B12 Longitudinal view of mitochondrial bioenergetics in skeletal muscle of premanifest transgenic minipig model for huntington's disease. (September 2018) - Rodinova, Marie; Krizova, Jana; Stufkova, Hana; Bohuslavova, Bozena; Askeland, Georgina; Dosoudilova, Zaneta; Juhas, Stefan; Ellederova, Zdenka; Zeman, Jiri; Eide, Lars; Motlik, Jan; Hansikova, Hana
Abstract : Background: Skeletal muscle wasting and atrophy is one of the severe clinical impairment connected with progression of Huntington's disease (HD). Mitochondrial dysfunction may play significant role in aetiology of the HD but exact condition of mitochondria as the major energy-producing organelles during development of the HD in muscle has not yet been carefully investigated. The aim of the study was the longitudinal monitoring of mitochondrial function in skeletal muscle of transgenic minipigs expressing the N-terminal part of human mutated huntingtin (TgHD). We investigated muscle (q. femoris) from 24, 36, 48 and 66 month old TgHD and age-matched wild-type (WT) siblings (6 TgHD + 6 WT in each age). Methods: Respiratory chain complexes (RCC), citrate synthase (CS), pyruvate dehydrogenase (PDH) activity and levels were analyzed by spectrophotometric, radioisotope and immunoelectrophoretic methods. Respiration was measured by polarography. Ultrastructure was analyzed by transmission electron microscopy. Genome integrity was assessed by q-PCR. The effect of HD, gender and aging were statistically analyzed. Results: Ultrastructural analyses in 48 month-old TgHD revealed local disorganization of myotubules, dilatation of sarcoplasmic reticulum, increased content of glycogen, higher density of mitochondria and incipient cristae disarrangement in comparison with WT. Activity of CS and RCC complex IV were significantly decreased in TgHD. Oxygen consumption showed significantly decreased ratio CII/CIV in TgHD contrary to WT. Protein analyses proved lower content of OPA1 protein which is necessary for correct mitochondrial fusion and quality control from 48 month-old TgHD animals. Genotype specific effect on mitochondrial DNA (mtDNA) damage but not on mtDNA copy number or nuclear DNA damage in TgHD was observed in the age of 66 month. Conclusions: Our results showed that mitochondrial function in muscle decreases slowly during premanifest stage of HD and biochemical phenotype appears at the age of 48 months. Mitochondrial disturbances may contribute to energetic depression of skeletal muscle in HD and are in concordance with mobility problems observed in this large animal model after 48 month of life. Supported by: Czech-Norwegian Research Programme 7F14308, NPUI LO1609 (MSMT), RVOVFN64165